Psychological capital and employee engagement as predictors of organisational citizenship behaviour in the industrial revolution 4.0 era: transfer of training as a mediator - Ting, Qian Hui; Lew, Tek Yew; Goi, Goi Chai Lee; Sim, Adriel; Gim, G.C.W. (2023)
Industrial Revolution 4.0 (IR4.0) offers vast potential in sustainable development through social progress and economic growth. Youths ought to take advantage of the sustainable development opportunities offered by IR4.0 in pursuit of the national agenda for sustainability. This study seeks to examine the relationships between psychological capital (PsyCap), employee engagement (EE), transfer of training (TOT), and organizational citizenship behaviour (OCB) among youth participants of IR4.0 in Sarawak. Data were collected from 251 working youths who were trained under Industrial Revolution 4.0 initiatives. Results revealed that PsyCap was positively related to EE, TOT, and OCB. EE and TOT were also found to be positively influence OCB. Additionally, TOT was found to mediate the relationship between PsyCap and OCB. This study contributes through the incorporation of digital competency into the TOT construct to examine the transfer of digital competencies. Besides, the model reflects the interplay between personal resource (PsyCap) and job resource (TOT) to influence effective organisational functioning (represented by OCB) through a motivational process. Findings suggest practical implications whereby organisations should engage pre-training psychological capital intervention to increase rate of training transfer whilst developing digital competencies of the workforce. Additionally, policymakers should formulate policies through training subsidies and tax exemptions for organisations to help strengthen youth conviction and resilience to facilitate their career progression.